Effect of frequency and duration of training on PHV between Swiss and Indonesian football clubs aged 9-11 years - Zahra Citra Fanita; Sri Sumartiningsih (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The aim of this research is to determine 1) the condition of Peak Height Velocity in La Sagne Groupement athletes and Tugumuda Semarang U9-U11 athletes, 2) is there an effect of frequency and duration on Peak Height Velocity, 3) is there a difference in Peak Height Velocity between Swiss and Indonesia clubs. The research used a quantitative descriptive research type with a comparative research design. The results showed that 1) Peak Height Velocity conditions for La Sagne Groupement FC athletes were 16.3 ± 1.3 (Mean ± SD) and Peak Height Velocity conditions for SSB Tugumuda were 14.0 ± 0.5 (Mean ± SD). 2) There is an effect of frequency and duration on Peak Height Velocity with the results of multiple regression analysis for frequency and duration. 3) There is a difference in PHV between the La Sagne de Groupement and SSB Tugumuda groups. The conclusion from this research there are differences PHV condition, there is an effect of duration and frequency of training on the PHV, and there are differences PHV value between La Sagne Groupement and SSB Tugumuda football clubs.